2009
DOI: 10.1029/2008jc004763
|View full text |Cite
|
Sign up to set email alerts
|

Gulf of Trieste: A changing ecosystem

Abstract: [1] Understanding the impact of climate change on zooplankton populations is of major importance, as they represent the basis for higher trophic levels in the marine food web. In this study we analyze the 36-year copepod abundance time series in the Gulf of Trieste, northern Adriatic, to investigate its interannual variability, with particular attention to species trends and phenology. Following the analysis of the local winter sea surface temperature, two periods are identified : 1970-1987 and 1988-2005. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 57 publications
1
57
0
Order By: Relevance
“…An obvious effect of such a decrease on the trophic dynamics of sardine in the region is that sardine would be forced to rely more heavily on primary producers as food. In addition, Conversi et al (2009) claimed that species of small copepods would most likely increase as a result of the anticipated warming of the Mediterranean Sea. This increase would impose additional limits on the expansion of phytoplankton species.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious effect of such a decrease on the trophic dynamics of sardine in the region is that sardine would be forced to rely more heavily on primary producers as food. In addition, Conversi et al (2009) claimed that species of small copepods would most likely increase as a result of the anticipated warming of the Mediterranean Sea. This increase would impose additional limits on the expansion of phytoplankton species.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an increasing appreciation that current climate change can trigger a major response in the structure and function of marine ecosystems on a decadal timescale, as has been observed in various parts of Correspondence to: G. I. Shapiro (gshapiro@plymouth.ac.uk) the World ocean including the North Atlantic and the North Sea (Reid et al, 2001) and the Mediterranean Sea (Conversi et al, 2009). Recent research demonstrates that changes in temperature, wind and river run-off may also play a role in changes of the Black Sea ecosystem (Daskalov, 2003;Oguz, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of positive relationships between ecological processes in the sea and NAO was observed in many studies, even though the underlying mechanisms often remain unexplained ( [18 The effects at the first levels of the trophic chain, that is on very short-lived species, are probably easier to identify ([18, and references therein] [25,68]) while those on fish and other high-trophic level organisms are far from being well understood. In the Mediterranean, Lloret et al [72] reported that the recruitment of continental shelf species, among which, E. cirrhosa, M. merluccius, and M. poutassou, was positively correlated with the river run-off and/or wind mixing index.…”
Section: Discussionmentioning
confidence: 99%
“…The regime shift recorded at the end of the 1980s has had direct effects on several marine ecosystem components encompassing more trophic levels and different Mediterranean basins (see [11,18], and references therein [19,24,25,49,50]). The environmental change observed in the Ionian Sea at the end of 1980s could have affected recruitment directly, through its effects on the survival rate of individuals from eggs to juveniles, or indirectly, through bottom-up effects of the changes in zooplanktonic species [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation